A critical evaluation of risk to reward ratio of quercetin supplementation for COVID‐19 and associated comorbid conditions. (8th April 2022) - Pawar, Anil; Russo, Maria; Rani, Isha; Goswami, Kalyan; Russo, Gian Luigi; Pal, Amit
Abstract: The interim results of the large, multinational trials on coronavirus disease 2019 (COVID‐19) using a combination of antiviral drugs appear to have little to no effect on the 28‐day mortality or the in‐hospital course. Therefore, there is a still vivid interest in finding alternate re‐purposed drugs and nutrition supplements, which can halt or slow the disease severity. We review here the multiple preclinical studies, partially supported by clinical evidence showing the quercetin's possible therapeutic/prophylaxis efficacy against severe acute respiratory syndrome coronavirus (SARS‐CoV) as well as comorbidities like chronic obstructive pulmonary disease (COPD), diabetes mellitus, obesity, coagulopathy, and hypertension. Currently, 14 interventional clinical trials are underway assessing the efficacy of quercetin along with other antiviral drugs/nutritional supplements as prophylaxis/treatment option against COVID‐19. The present review is tempting to suggest that, based on circumstantial scientific evidence and preliminary clinical data, the flavonoid quercetin can ameliorate COVID‐19 infection and symptoms acting in concert on two parallel and independent paths: inhibiting key factors responsible for SARS‐CoV‐2 infections and mitigating the clinical manifestations of the disease in patients with comorbid conditions. Despite the broad therapeutic properties of quercetin, further high power randomized clinical trials are needed to firmly establish its clinical efficacy against COVID‐19.